HCV RNA Quantification with Different Assays: Implications for Protease-Inhibitor-Based Response-Guided Therapy. Issue 6 (August 2014) - Fevery, Bart; Susser, Simone; Lenz, Oliver; Cloherty, Gavin; Perner, Dany; Picchio, Gaston; Sarrazin, Christoph
Background: Response-guided therapy (RGT) for HCV treatment, whereby therapy duration is shortened according to on-treatment virological response, requires patient HCV RNA concentrations below the lower limit of quantification (LLOQ) or limit of detection (LOD) of the viral load assay at weeks 4 and 12. Concordance of two assays and impact on treatment decisions were investigated. Methods: Plasma samples ( n =1, 411; baseline to week 12) from HCV genotype-1-infected patients ( n =290) receiving simeprevir (TMC435) plus pegylated interferon-α2a/ ribavirin in the PILLAR study (NCT00882908) were analysed using Roche High-Pure-System/COBAS® TaqMan® v2.0 assay (HPS; LLOQ 25 IU/ml and LOD 15 IU/ml; Roche Diagnostics, Indianapolis, IN, USA) and reanalysed using Abbott RealTime assay (ART; LLOQ and LOD 12 IU/ml; Abbott Molecular Inc., Des Plaines, IL, USA). Results: Overall, 217/766 (28.3%) samples from different time points with HCV RNA undetectable by HPS had HCV RNA detectable by ART. Conversely, 35/584 (6.0%) samples undetectable by ART were detectable by HPS. For both assays, most discrepant samples (96–100%) had HCV RNA<25 IU/ ml. At week 4, 75.5% of samples were undetectable by HPS, whereas 49.4% were undetectable by ART, resulting in different RGT assessment in 26.1% ( P <0.0001). At week 12, 95.4% and 91.9% of samples were undetectable with HPS and ART, respectively. Conclusions: Lower rates of undetectable HCV RNA with ART at week 4 suggest that if RGT criteria are determined with ART, the proportion of patients qualifying for shorter treatment duration may be significantly lower (26%). Therefore, different RGT criteria may be necessary for ART to maximize numbers benefiting from shortened treatment. Further testing and validation are required.